The Effect of Risk Management and Company Size on Financial Performance - Anisa Fawwaziah; Ida Rosnidah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study, which generated 32 observations, attempts to look at the effects of business size also risk management on financial performance in state-owned banking institutions listed on the IDX (Indonesia Stock Exchange) between 2017 and 2024. Return on Assets (ROA), a financial performance metric, is the investigation's dependent variable, while the independent variables are risk management, which is represented by Non-Performing Loans (NPL), and firm size, which is determined by the natural logarithm of total assets. Multiple linear regression analysis is the method of data analysis employed. The results of the investigation demonstrate that risk management significantly and negatively affects the financial performance of state-owned banks, with a t-value of 4.611 also a significance level of 0.001, meaning that the lower the NPL, the better the financial performance. Conversely, company size was found to have a positive also significant impact on financial performance with a t-value of 7.073 also a significance level of 0.001, confirming the financial intermediation function's economies of scale claim. Simultaneously, with a F value of 52.776 and a coefficient of determination (Adjusted R Square) of 77.0%, risk management and company size have a favorable also substantial effect on financial performance. This study helps to the growth of financial intermediation theory in the context of Indonesian state-owned banks and provides practical implications for state-owned bank management and investors in making strategic decisions related to risk management and business scale optimization to improve financial performance.